PELAKSANAAN PERSONAL SELLING DAN PENGARUHNYA TERHADAP PENINGKATAN PENJUALAN (kasus pada PT. ARTHA PRIMA FINANCE PEKANBARU) - James Alfino; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The development in pekanbaru city causes the competition in business world is increasingly fierce. One of them is that perceived by leasing company. The companies involved in that fierce competition have to be able to size the market share as much as they could. PT. Artha Prima Finance Pekanbaru maximizing personal selling in facing the competition increase sales. Based on the phenomenom above, the writer was interested to investigate the personal selling activities performed by PT. Artha Prima Finance Pekanbaru. This study was conducted at PT. Artha Prima Finance Pekanbaru, located on tuanku tambusai street, pekanbaru. The writer took the PT. Artha Prima Finance Pekanbaru agents as the key informant, the customers as the population, and 80 people of the population to be the sample in this study. The researcer gatered the data both primer and secondary. The data collection techniques used in this research were questionnaire and interview, and used descriptive analysis as the data analysis technique. Company’s business activities focused on the four-wheeled vehicle financing, both commersial and private vehicles, both new and secondhand. The reserch finding showed that the respondent considered the personal selling performed by PT. Artha Prima Finance Pekanbaru could be categorized “good”. The seven indikator of personal selling in this reserch involved customer searcing, directing, communicating, salling, servicing, information gathering and alocating gained positive response from the responden.Key word :analysis, personal selling activities, selling